Strategi Pemasaran Terintegrasi dalam Pengambilan Keputusan Pengajuan Kredit - Ghozali, Ghozali; Nuraeni, Eny; Novita, Mega D. (Jurnal Manajemen & Budaya, 2024)
This research aims to identify the influence of Personal Selling, Service Quality, Business Location, and Digital Marketing on Credit Application Decisions at the ‘Sumber Manis’ Prajurit Kulon Farming Cooperative, Mojokerto City. This research uses a quantitative approach with a sample of 30 cooperative customers. The results of the F test show that these four variables have a simultaneous effect on the Credit Application Decision. The variables Personal Selling, Service Quality, Business Location, and Digital Marketing also partially have a positive influence on Credit Application Decisions. The results of this research provide deeper insight into various aspects of marketing in the context of credit application decisions in cooperatives. The practical implication is that cooperatives and similar financial institutions can improve their marketing strategies by considering the key roles played by Personal Selling, Service Quality, Business Location, and Digital Marketing in shaping customer perceptions and decisions. This research also supports previous findings which state that marketing aspects have an important role in influencing customer decisions regarding credit applications.